2023
DOI: 10.3389/fpls.2023.1189747
|View full text |Cite
|
Sign up to set email alerts
|

Silage additives improve fermentation quality, aerobic stability and rumen degradation in mixed silage composed of amaranth and corn straw

Abstract: The objective of this research was to investigate effects of different additives on the fermentation quality, aerobic stability and rumen degradation of mixed silage composed of amaranth and corn straw. The mixture ratio of amaranth to corn straw was 78%: 22%. Three additives were selected in this study and five groups were as follows: control group (CON, without additive), lactic acid bacteria group (LAB, 5 mg/kg, Lactobacillus plantarum ≥ 1.6×1010 CFU/g and L. buchneri ≥ 4.0×109 CFU/g), glucose group (GLU, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…By the action of microorganisms, WSC are depleted and degraded into organic acids. However, amaranth did not have a high WSC content, and the low number of LAB attached to the raw material does not allow for the production of sufficient LA to lower the pH of the silage (Ma et al, 2023), which is compatible with the results of high pH and low LA content in the present study. In addition, inoculation with L. plantarum promoted homofermentation and prevents organic degradation caused by insufficient LA production (Ren et al, 2020), which is conducive to reducing nutrient losses.…”
Section: Discussionsupporting
confidence: 86%
“…By the action of microorganisms, WSC are depleted and degraded into organic acids. However, amaranth did not have a high WSC content, and the low number of LAB attached to the raw material does not allow for the production of sufficient LA to lower the pH of the silage (Ma et al, 2023), which is compatible with the results of high pH and low LA content in the present study. In addition, inoculation with L. plantarum promoted homofermentation and prevents organic degradation caused by insufficient LA production (Ren et al, 2020), which is conducive to reducing nutrient losses.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the high carbohydrate content in sweet sorghum, it can provide energy for rumen microorganisms. Ma et al (2023) have shown that adding lactic acid bacteria additive to mixed silage of amaranth and corn straw can effectively improve the degradation of dry matter [64]. Microbial fermentation of sugars and organic acids in crops releases gases such as carbon dioxide and hydrogen, which leads to dry matter loss [57].…”
Section: Degradation Rates Of Dm Cp Adf Ndf and Adl In The Rumen Of S...mentioning
confidence: 99%
“…Therefore, aerobic stability is an important factor affecting the nutritional quality and subsequent feeding value of silage in ruminants [29]. Aerobic microorganisms metabolize and consume nutrients, and a change in silage temperature is usually used as an important parameter to evaluate the aerobic stability of silage [41].…”
Section: Effect Of Moisture Content and Additives On The Aerobic Stab...mentioning
confidence: 99%